The Role and Meaning of the Free Time in Context of Formation of Socio-Cultural Values in Modern Armenian Society - Mkoyan, Gohar (Տիգրան Մեծ)
The article considers the problem of a culture of free time as a factor in the formation of modern society that has entered the era of globalization – with the respective opportunities for a variety of leisure activities and, at the same time, it may assume problematic situations for the person related to the effective use of leisure potential for the development of leisure culture of the person. The aim of this study was to examine the role and free time value in the formation of social and cultural values in our society between two generations - today's youth (18 to 30 years) and the older generation (56 to 66 years), to identify the particular preferences in the environment of two generations in the field of leisure, to provide a comparative analysis and assessment of the data. The author had the task of considering the organization of free time as scientific and social problems, its effective implementation representatives of the two age groups, the disclosure of the content of free time of concept of culture. The research has used quantitative and qualitative methods of sociologi-cal research – unstructured data included observations, expert study using unstructured in-depth interviews, the survey (questionnaires), interviews by stratificat sampling in compliance with the proportions of the population structure by sex and age.
Keywords: Culture